A comprehensive analysis on the safety of two biologics dupilumab and omalizumab - Xiao, Yu; Yang, Wanying; Wang, Muyang (Frontiers in Medicine, 2024)
Dupilumab was approved for the treatment of several dermatologic immune-mediated inflammatory diseases, such as atopic dermatitis and bullous pemphigoid; whereas omalizumab is the first biological agent which was approved to treat chronic spontaneous urticaria. None of the published meta-analyses has provided the sufficient data regarding the safety of these two biologics, especially regarding their potential serious adverse events (SAEs). The aim of this study was, to comprehensively evaluate the safety of the two biologics dupilumab and omalizumab. In this study, we included 32 randomized trials, and performed meta-analyses on 113 types of SAEs regarding dupilumab and 61 types of SAEs regarding omalizumab. We identified that: (1) use of dupilumab was significantly associated with the lower incidence of atopic dermatitis, while use of omalizumab was significantly associated with the lower incidence of asthma; and (2) use of dupilumab was not significantly associated with the incidences of 112 other kinds of SAEs including various infectious diseases, while use of omalizumab was not significantly associated with the incidences of 60 other kinds of SAEs including various infectious diseases. This meta-analysis for the first time assessed the association between use of dupilumab or omalizumab and incidences of various SAEs, and identified that neither dupilumab use nor omalizumab use was associated with the increased risks of any SAEs including various infectious diseases. These findings further confirm the general safety of the two biologics dupilumab and omalizumab. This informs clinicians that there is no need to worry too much about the safety issues of these two biologics.